Prostaglandin D(2) Inhibits Hair Growth and Is Elevated in Bald Scalp of Men with Androgenetic Alopecia - Garza, Luis A. (2012)
Testosterone is necessary for the development of male pattern baldness, known as androgenetic alopecia (AGA); yet, the mechanisms for decreased hair growth in this disorder are unclear. We show that prostaglandin D(2) synthase (PTGDS) is elevated at the mRNA and protein levels in bald scalp compared to haired scalp of men with AGA. The product of PTGDS enzyme activity, prostaglandin D(2) (PGD(2)), is similarly elevated in bald scalp. During normal follicle cycling in mice, Ptgds and PGD(2) levels increase immediately preceding the regression phase, suggesting an inhibitory effect on hair growth. We show that PGD(2) inhibits hair growth in explanted human hair follicles and when applied topically to mice. Hair growth inhibition requires the PGD(2) receptor G protein (heterotrimeric guanine nucleotide)–coupled receptor 44 (GPR44), but not the PGD(2) receptor 1 (PTGDR). Furthermore, we find that a transgenic mouse, K14-Ptgs2, which targets prostaglandin-endoperoxide synthase 2 expression to the skin, demonstrates elevated levels of PGD(2) in the skin and develops alopecia, follicular miniaturization, and sebaceous gland hyperplasia, which are all hallmarks of human AGA. These results define PGD(2) as an inhibitor of hair growth in AGA and suggest the PGD(2)-GPR44 pathway as a potential target for treatment.